2021
DOI: 10.3389/fnins.2021.699999
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Neuroimaging Predictors of Learning Performance of Sensorimotor Rhythm Up-Regulation Neurofeedback

Abstract: Electroencephalographic (EEG) neurofeedback (NFB) is a popular neuromodulation method to help one selectively enhance or inhibit his/her brain activities by means of real-time visual or auditory feedback of EEG signals. Sensory motor rhythm (SMR) NFB protocol has been applied to improve cognitive performance, but a large proportion of participants failed to self-regulate their brain activities and could not benefit from NFB training. Therefore, it is important to identify the neural predictors of SMR up-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Indeed, the amplitude of the signal measured during the resting state EEG or the first session seems to be a reliable predictor of an individual's ability to modulate this signal, in that the higher the level of baseline activity, the greater the modulation. This has been observed for the alpha (Su et al, 2021;Wan et al, 2014), sensorimotor rhythm (SMR, Blankertz et al, 2010;Li et al, 2021;Reichert et al, 2015;Weber et al, 2011) and low beta bands (12-15 Hz, Nan et al, 2015;Sho'ouri, 2021). Interestingly, although most of the cited studies aimed to increase the amplitude of the target signal during the resting state, one study (Nan et al, 2018) showed that a lower amplitude of the trained alpha frequency also predicted the ability to decrease it during NFB training.…”
Section: E Predictors Of Neurofeedback Successmentioning
confidence: 89%
“…Indeed, the amplitude of the signal measured during the resting state EEG or the first session seems to be a reliable predictor of an individual's ability to modulate this signal, in that the higher the level of baseline activity, the greater the modulation. This has been observed for the alpha (Su et al, 2021;Wan et al, 2014), sensorimotor rhythm (SMR, Blankertz et al, 2010;Li et al, 2021;Reichert et al, 2015;Weber et al, 2011) and low beta bands (12-15 Hz, Nan et al, 2015;Sho'ouri, 2021). Interestingly, although most of the cited studies aimed to increase the amplitude of the target signal during the resting state, one study (Nan et al, 2018) showed that a lower amplitude of the trained alpha frequency also predicted the ability to decrease it during NFB training.…”
Section: E Predictors Of Neurofeedback Successmentioning
confidence: 89%
“…Differences in brain anatomy and physiology, such as cortical thickness, white matter integrity, and neurotransmitter receptor distribution, could affect neurofeedback learning rates and outcomes (Haugg et al, 2020;Li et al, 2021;Misaki et al, 2019;Ninaus et al, 2015;Tsuchiyagaito et al, 2021b;Weber et al, 2020;Zhao et al, 2021). However, the literature has yet to fully explore and integrate these individual differences.…”
Section: Practical Challenges In Neurofeedback Implementationmentioning
confidence: 99%
“…Further, some studies reported structural correlators of neurofeedback learning performance, such as gray matter volume of the right middle cingulate cortex and white matter volume of the cingulate tract for frontal-midline theta neurofeedback training [13], and gray matter volumes in the supplementary motor area and left middle frontal gyrus for gamma neurofeedback training [14]. A previous study by our group pointed out that the neurofeedback learning ability is related to both structural and functional brain imaging features [15]. However, no neuroimaging predictors for FAA neurofeedback protocol have been reported so far.…”
Section: Introductionmentioning
confidence: 99%